The relationship between enthalpy of immersion, and its derived wettability parameters, to flotation response - Taguta, Jestos (Department of Chemical Engineering, 2019)
The wettability of mineral surfaces plays an important role in the flotation process. A wettable mineral is hydrophilic while a non-wettable mineral is hydrophobic. In the flotation process, sufficiently hydrophobic particles are collected by rising air bubbles and they report to the concentrate. On the other hand, hydrophilic particles do not attach to the air bubbles and they report to the tailings. Some of the conventional methods used to characterise mineral surface wettability include contact angle, inverse gas chromatography (iGC), time of flight secondary ion mass spectrometry (ToF-SIMS) and induction time measurements. The measurement of contact angles on flat, smooth and ideal surfaces is relatively simple, straight forward and well-described, but the measurement of powder contact angles is not so straight forward. The iGC technique is a gas phase technique while ToF-SIMS exposes the particles under high vacuum compared to an aqueous environment in real flotation systems. This thesis has investigated the use of the enthalpy of immersion as an indicator of the wettability of mineral surfaces. The enthalpy of immersion is the heat change arising from the replacement of the solid-gas interface with the solid-liquid interface when a solid surface is immersed in a liquid. Although immersion calorimetry has been established as a reliable means of determining the wettability of solid surfaces, it has found only limited applications in flotation research where wettability of mineral ores is a key variable. In this study, precision solution calorimetry was employed to measure the enthalpies of immersion of different minerals in water. The Washburn method and a microflotation system were used to measure the corresponding powder contact angles and the flotation responses of the same minerals respectively. Two mineral systems were investigated in this study, viz: different pure minerals in their natural form as well as collector-coated sulphide minerals. Furthermore, to assess whether the enthalpy of immersion is able to differentiate between the amounts of minerals of different wettabilities in a mineral mixture, a synthetic ore comprising of different proportions of a sulphide mineral (realgar) and a silicate gangue mineral(albite) was also investigated. The surface energetics of different minerals and the synthetic ore were also characterised by measuring the enthalpies of immersion in different probe liquids and applying the van Oss-Chaudhury-Good (VOCG) model. The VOCG model is reported to give consistent results in terms of surface energetics of surfaces. It has been found that the enthalpy of immersion technique was capable of distinguishing differences in the wettabilities of different minerals and these differences were explained in terms of the solid state properties of the minerals. The enthalpy of immersion method was also able to assess the changes in the surface chemical properties of the galena and realgar surfaces resulting from collector adsorption. The magnitude of the enthalpy of immersion was inversely related to the surface coverage of potassium amyl xanthate on both galena and realgar. The enthalpy of immersion measurements correlated well with powder contact angle measurements, but, most importantly, the enthalpy of immersion measurements were found to be more reproducible and sensitive than the contact angle measurements. It has also been shown that the enthalpy of immersion is a more widely applicable measure of the hydrophobicity of mineral particles typical of those used in the flotation process as opposed to the contact angle. It is therefore concluded that the enthalpy of immersion is a superior indicator of the extent to which minerals are hydrophobic or hydrophilic either in their natural form or after treatment with a collector. Furthermore, it was found that there was a strong inverse relationship between the enthalpy of immersion of the minerals studied and their flotation response. The strong inverse relationship has potential to be used in pulp phase flotation models, although this was not the focus of this thesis. In addition, a value, termed the critical enthalpy of immersion (CEI), was observed above which no flotation occurred. The CEI was in the region of -200 mJ/m². At values less exothermic than the CEI, the flotation response was found to be inversely related to the enthalpy of immersion. At values more exothermic, viz. more negative, than the CEI, no flotation occurs. The significance of this finding is that for any mineral whose flotation behaviour is unknown, the measurement of the enthalpy of immersion appears to be able to predict the flotation response of the mineral. The variance in the inverse relationship between enthalpy of immersion and rate of flotation was reduced when the data was normalized with respect to particle density which was the only variable in the flotation studies in terms of particle-bubble encounter efficiency. These results have shown that the enthalpy of immersion is an excellent indicator of both the natural mineral hydrophobicity and of the extent to which collectors render a mineral hydrophobic. The relative strength of the acid-base sites was shown to depend on the mineral type. The surface energetics obtained in this study were consistent with the hydrophobichydrophilic nature of these minerals. The basic, polar components as well as the total surface energy decreased in the following order: silicates > metallic sulphide minerals and talc. It was observed that the higher the total surface energy, the lower the hydrophobicity of the mineral. The acid-base characteristics of the minerals, measured by solution calorimetry, can give a detailed insight into the surface energies of different mineral types and may be useful in optimising processing strategies. Using the surface energetics, two important parameters were calculated, viz: the interfacial free energy of interaction between mineral particles and bubbles immersed in water (∆Gpwb) as well as the work of adhesion for water (Wadh). Interestingly, and not surprisingly, the trends in both of these parameters coincided with the trend in the enthalpies of immersion of the different minerals in water. Critical values of ∆Gpwb and Wadh parameters in the region of 200 mJ/m² and 320 mJ/m² respectively were observed above which no flotation occurs. At values less than the critical values, both parameters were inversely related to the flotation response. The enthalpy of immersion was able to differentiate between the amounts of minerals of different wettabilities in a mineral mixture. The enthalpy of immersion became increasingly exothermic as the percentage of albite in the realgar-albite mixtures increased. The experimentally determined enthalpies of immersion in water were in excellent agreement with the weighted enthalpies of immersion for the realgar-albite mixtures. The weighted enthalpies of immersion of the synthetic ore were calculated based on the specific surface areas of both realgar and albite. Therefore, it is possible to calculate the enthalpy of immersion of a synthetic ore (mineral mixtures) from the knowledge of the proportion and the enthalpy of immersion in water of the individual minerals comprising the synthetic ore. The surface energetics of the synthetic ore showed that there is a relationship between the mass recovery and the calculated relative surface polarity, based on the individual polar and total surface energies. As the relative surface polarity increases, there is a significant decrease in the mass recovery after a relative surface polarity of about 0.4. Thus, the enthalpy of immersion has the potential to be used to predict the wettability and the floatability potential of mineral mixtures. It is proposed that this work should be extended to other mineral mixtures, with careful measurement and calculation of the surface energetics of these mixtures. Thus, this work presents an opportunity for further study to investigate the use of the enthalpy of immersion to characterise the wettability of real ores.